Dynamic properties of reinforced concrete building through the microtremor measurement - Liquido, Surtalicito C.; Ogawa, Junji; Pichai Nimityongskul; Wireland, Martin; The Government of Japan (Bangkok : Asian Institute of Technology, 1981)
Digital data of microtremor vibrations are available, taken from 16 medium-rise (2 to 9 storey) reinforced concrete buildings. For each building, these vibration data were taken simultaneously from the ground and the roof in the two horizontal directions. Microtremor vibrations are very low amplitude motions and are caused by very small earthquakes and by the continuous motion of the ground caused by man-made disturbances as machinery, vehicle traffic and etc. The fundamental period and the corresponding damping ratio of each building were estimated thru the analysis of the data. Three methods of analysis were used: the power spectrum analysis, the running Fourier spectrum analyzes is and the autocorrelation analysis. Some form of smoothing was used in the first two methods. A plotter machine was used extensively in all the methods in plotting the results where the fundamental values were estimated. The advantages and the disadvantages of t he three methods were discussed in terms of the convenience of obtaining the fundamental values, the computer time and the possibility of estimating the higher frequencies and the corresponding damping ratios. Approximately the same value of the fundamental period and a range of values for the corresponding damping ratio were obtained by the three methods for each building.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Structural dynamics; Reinforced concrete construction